Karakteristik pasien fraktur kruris di RSUD Sanjiwani Gianyar tahun 2020 - Gede Agastya Pracheta Ewari; Yoga Premana (Intisari Sains Medis, 2021)
Background: The location of the most fractures in traffic accident victims is the lower extremity bone. Data from the Basic Health Research (Riskesdas) also shows that fractures in the lower extremities due to traffic accidents have the highest prevalence among other fractures. Cruris fractures generally occur as a result of high-energy trauma such as a traffic accident or low-energy torsional trauma. The increase in cases of trauma, especially traffic accidents cause an increase in the incidence of tibial and fibular fractures. This study aims to determine the prevalence and characteristics of cruris fractures at the Sanjiwani Hospital, Gianyar in 2020.Methods: The design of this study was retrospective descriptive using 30 samples of cruris fractures taken from secondary data from patient medical records at the Sanjiwani Hospital, Gianyar. The variables of this study included gender, age, cause of fracture and type of cruris fracture. Data analysis using SPSS software.Results: The most common fractures of the tibia and fibula occurred in male patients (56%). The age group most frequently experiencing cruris fractures is the adult age (18-59 years). The most common cause of cruris fractures was traffic accidents as many as 19 people (64%). The most common type of cruris fracture found in this study was a fracture of the tibia fibula as many as 21 people (70%).Conclusion: The most common cruris fractures are tibia and fibula fractures in men, with the most common cause of traffic accidents. This study is expected to be able to become a basic data material for conducting a wider study on the prevalence and characteristics of cruris fractures in Bali, so that the public can be more aware of the incidence of fractures that still occur frequently. Latar belakang: Lokasi fraktur terbanyak pada korban meninggal kecelakaan lalu lintas adalah pada tulang bagian ekstremitas bawah. Data dari Riset Kesehatan Dasar (Riskesdas) juga menunjukkan bahwa fraktur pada ekstremitas bawah akibat kecelakaan lalu lintas memiliki prevalensi yang paling tinggi diantara fraktur lainnya. Fraktur kruris pada umumnya terjadi akibat trauma dengan energi tinggi seperti kecelakan lalu lintas atau trauma torsional energi rendah. Peningkatan kasus trauma, terutama kecelakaan lalu lintas menyebabkan peningkatan insidens fraktur tibial dan fibular. Penelitian ini bertujuan untuk mengetahui prevalensi dan karakteristik dari fraktur kruris di RSUD Sanjiwani Gianyar pada tahun 2020.Metode: Rancangan penelitian ini adalah deskriptif retrospektif dengan menggunakan 30 sampel fraktur kruris yang diambil dari data sekunder rekam medis pasien di RSUD Sanjiwani Gianyar. Variabel penelitian ini meliputi jenis kelamin, usia, penyebab fraktur dan jenis fraktur kruris. Analisa data menggunakan perangkat lunak SPSS.Hasil: Fraktur tibia dan fibula paling banyak terjadi pada pasien laki – laki (56%). Kelompok usia yang paling sering mengalami fraktur kruris adalah usia dewasa (18 – 59 tahun). Penyebab terbanyak fraktur kruris adalah kecelakaan lalu lintas sebanyak 19 orang (64%). Jenis fraktur kruris tersering yang ditemukan pada penelitian ini adalah fraktur tibia fibula sebanyak 21 orang (70%).Simpulan:  Fraktur kruris paling banyak didapatkan adalah fraktur tibia dan fibula pada laki-laki, dengan penyebab tersering kecelakaan lalu lintas. Penelitian ini diharapkan mampu menjadi bahan data dasar untuk dilakukannya penelitian lebih luas mengenai prevalensi dan karakteristik fraktur kruris di Bali, sehingga masyarakat dapat lebih waspada mengenai kejadian fraktur yang masih sering terjadi.